Oscillation and Asymptotic Behavior of Second Order Half Linear Neutral Dynamic Equations - Ahmed, Faten Abbas; Mohamad, Hussain Ali (Iraqi Journal of Science, 2022)
The oscillation property of the second order half linear dynamic equation was studied, some sufficient conditions were obtained to ensure the oscillation of all solutions of the equation. The results are supported by illustrative examples.